Dysregulated CD46 shedding interferes with Th1‐contraction in systemic lupus erythematosus - Ellinghaus, Ursula (Eur J Immunol, 2017)
IFN‐γ‐producing T helper 1 (Th1) cell responses mediate protection against infections but uncontrolled Th1 activity also contributes to a broad range of autoimmune diseases. Autocrine complement activation has recently emerged as key in the induction and contraction of human Th1 immunity: activation of the complement regulator CD46 and the C3aR expressed by CD4(+) T cells via autocrine generated ligands C3b and C3a, respectively, are critical to IFN‐γ production. Further, CD46‐mediated signals also induce co‐expression of immunosuppressive IL‐10 in Th1 cells and transition into a (self)‐regulating and contracting phase. In consequence, C3 or CD46‐deficient patients suffer from recurrent infections while dysregulation of CD46 signaling contributes to Th1 hyperactivity in rheumatoid arthritis and multiple sclerosis. Here, we report a defect in CD46‐regulated Th1 contraction in patients with systemic lupus erythematosus (SLE). We observed that MMP‐9‐mediated increased shedding of soluble CD46 by Th1 cells was associated with this defect and that inhibition of MMP‐9 activity normalized release of soluble CD46 and restored Th1 contraction in patients’ T cells. These data may deliver the first mechanistic explanation for the increased serum CD46 levels observed in SLE patients and indicate that targeting CD46‐cleaving proteases could be a novel avenue to modulate Th1 responses.